Digital signal processing fundamentals - Ashfaq A. Khan (Da Vinci Engineering Press, 2005)
Digital Signal Processing (DSP), as the term suggests, is the processing of signals using digital computers. These signals might be anything transferred from an analog domain to a digital form (e.g., temperature and pressure sensors, voices over a telephone, images from a camera, or data transmittal though computers). As a result, understanding the whole spectrum of DSP technology can be a daunting task for electrical engineering professionals and students alike. Digital Signal Processing Fundamentals provides a comprehensive look at DSP by introducing the important mathematical processes and then providing several application-specific tutorials for practicing the techniques learned. Beginning with general theory, including Fourier Analysis, the mathematics of complex numbers, Fourier transforms, differential equations, analog and digital filters, and much more; the book then delves into Matlab and Scilab tutorials with examples on solving practical engineering problems, followed by software applications on image processing and audio processing-- complete with all the algorithms and source code. This is an invaluable resource for anyone seeking to understand how DSP works